Right Coronary Artery Anomaly Coursing on the Right Atrium in a Patient Undergoing Coronary Artery Bypass Grafting (Annals of Medical Research, 2021)
None
Keywords: Coronary Vessel Anomaly; Coronary Artery Bypass; Coronary Disease.